Pengaruh Pengetahuan, Sikap dan Kepribadian terhadap Perilaku Anggota dalam Mengelola Keuangan - Nuraminanti, Putri Syarah; Wazdi, Adi Indradi; Nurkamali AZ, Ahmad (Ma'soem University, 2024)
Based on the results of observations, that the background of this research is the decline in the number of members in the last 2 years and the lack of public knowledge of the Cooperative. This study aims to determine how knowledge, attitudes and personality influence the behavior of members of the IKOPIN Jatinangor Big Family Cooperative. The object of research in this thesis is members of the IKOPIN Jatinangor Big Family Cooperative. The type of research is quantitative associative with primary data and uses data collection techniques in the form of observations, interviews, literature studies and questionnaires. The sampling technique is non probability sampling with convenience sampling type. The population is all members in the IKOPIN Jatinangor Big Family Cooperative, totaling 1,147 people with a sample of 100 people. The results showed that there was a significant influence between knowledge on the behavior of members; there was a significant influence between attitudes towards member behavior; there is a significant influence between personality on member behavior and simultaneously there is a significant influence of knowledge, attitudes and personality on member behavior at the IKOPIN Jatinangor Big Family Cooperative.